Energy, the state, and the market British energy policy since 1979 - Helm, Dieter (Oxford : Oxford University Press, 2010)
Helm provides a broad and lively survey of British energy policy since 1979. He traces the way in which political pressures from the proponents of both nationalization and privatization have affected the development of an industry which forms a significant part of the national economy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Energy policy -- Great Britain; Energy industries -- Great Britain